Ceragenins exhibit bactericidal properties that are independent of the ionic strength in the environment mimicking cystic fibrosis sputum - Skłodowski, Karol; Suprewicz, Łukasz; Chmielewska-Deptuła, Sylwia Joanna; Kaliniak, Szczepan; Okła, Sławomir; Zakrzewska, Magdalena; Minarowski, Łukasz; Mróz, Robert; Daniluk, Tamara; Savage, Paul B.; Fiedoruk, Krzysztof; Bucki, Robert (Frontiers in Microbiology, 2023)
The study investigated the effect of sodium chloride (NaCl) on the antimicrobial efficacy of the cathelicidin LL-37, and their synthetic mimetic ceragenins (Ceragenins), which are considered as potential therapeutic agents in cystic fibrosis (CF) lung infections. The susceptibility of cystic fibrosisassociated bacterial pathogens (Pseudomonas aeruginosa, Ochrobactrum spp. and Staphylococcus aureus) and fungal pathogens (Candida albicans and C. tropicalis) to these compounds was determined using Minimum Inhibitory Concentrations (MIC) and Bactericidal Concentrations (MBC) tests in sputum samples collected from patients diagnosed with CF. Furthermore, a colony-counting assay was used to assess the effect of varying NaCl concentrations on tested agents' antimicrobial activity.The findings reveal that ceragenins exhibit potent antimicrobial activity in CF sputum, regardless of the NaCl concentration when compared to LL-37 and omiganan. Given the broad-spectrum antimicrobial activity of ceragenins in microenvironments resembling the airways of CF patients, they represent promising agents for managing CF disease. This manuscript aligns with the journal's scope as it contributes to the field of microbiology and infectious diseases. The investigation provides valuable insights into the development of effective antimicrobial strategies to combat CF-associated infections.